Family Health Clinical Officers: Key professionals to strengthen primary healthcare in Kenya - Katherine Linley (AOSIS, 2024)
Primary healthcare (PHC) is recognised as the means to achieve universal health coverage, a national priority for Kenya. With only approximately 200 family physicians for a population of over 54 million, innovative solutions for providing quality PHC are needed. Clinical Officers, as mid-level health workers, already provide much of the primary care across Kenya, but without specialised training. To provide highly trained Family Health practitioners, a Higher Diploma in Family Health for Clinical Officers (FHCO) was launched by the government in 2018. With experience in delivering innovative and strategic higher diplomas, AIC Kijabe Hospital has been involved in curriculum development of this new diploma since its inception, and in October 2021 the first cohort of FHCO trainees was admitted to Kijabe College of Health Science, graduating in 2023. The second cohort is underway with plans for an annual intake. The FHCO graduates are running Family Medicine clinics at AIC Kijabe Hospital and its satellite clinics and are heavily involved in teaching. They are well-trained to deliver comprehensive, evidence-based, cost-effective and holistic care. As the programme expands, we expect graduates to be working across the country and leading efforts in enhancing the health and well-being of individuals, families and communities within primary healthcare networks (PCNs). By training FHCOs, this higher diploma is an efficient and cost-effective way to improve PHC, particularly for underserved Kenyans, and thus is a key part of enabling the Kenyan Government to achieve universal health coverage. This model of training could easily be replicated in other countries.